KUALITAS PELAYANAN PUBLIK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT KOTA KENDARI - Murniati; Riston G. Ahmad; Dahniar (Halu Oleo University, 2024)
government income, particularly in Southeast Sulawesi Province. This study aims to analyze the impact of public service quality at the One-Stop Administration System Office (SAMSAT) in Kendari City on the compliance level of motor vehicle taxpayers. Data revealed that in 2023, the taxpayer compliance rate in Kendari City dropped to 68.50%, with 45,556 taxpayers out of 144,634 failing to fulfil their obligations. The findings indicate that the quality of public services, including accessibility, speed of service, clarity of information, and courteous attitudes of officers, significantly influence taxpayer satisfaction and compliance. From 2021 to 2023, the realization of regional tax revenues consistently exceeded the targets, with an average achievement rate of 147.33%. However, challenges remain in maintaining consistent taxpayer compliance. Factors influencing compliance include taxpayers' understanding of their tax obligations, the quality of services provided by tax authorities, and public awareness of the importance of tax contributions to regional development. This study concludes that improving public service quality at the SAMSAT Office in Kendari City is a crucial strategy for enhancing taxpayer compliance and optimizing local revenue.